Cardiac effects of a competitive road race in trained child runners - Rowland, T.; Goff, D.; DeLuca, P.; Popowski, B. (Pediatrics, 1997)
BACKGROUND: Animal studies and investigations of adult endurance athletes indicate a transient depression of myocardial function after prolonged high-intensity exercise. PURPOSE: To determine whether a similar decrease is observed in child distance runners after a 4-km competitive road race. METHODS: Anthropometric measures, resting M-mode echocardiograms, maximal cycle exercise tests with estimation of cardiac output, and electrocardiograms were performed before a 4-km road race in nine run-trained boys (mean age, 12.2 years). Weight and resting echocardiogram and electrocardiogram were assessed immediately after the race. The entire test battery was repeated 24 hours later. RESULTS: Small but significant decreases in mean body weight and left ventricular end-diastolic dimension were observed immediately after the race, but there were no changes in shortening fraction. These findings are consistent with the effects of dehydration. Measurements returned to prerace values by 24 hours of recovery. Peak work capacity, maximal stroke volume, and maximal cardiac output were similar on prerace and 24-hour-postrace testing. No electrocardiographic abnormalities were observed. CONCLUSIONS: No adverse cardiac effects were observed from a competitive 4-km road race in male child distance runners.